Solid-phase synthesis of fused 1,4-diazepanone peptidomimetics via tandem N-iminium ion cyclization-nucleophilic addition - Ventosa Andrés, Pilar (2015)
We herein describe the solid-phase synthesis of protected N-oxoalkyl-derivatized peptides designed for subsequent acid-mediated, tandem N-acyliminium ion cyclization-nucleophilic addition reaction. The target compounds contained fused 1,4-diazepanones incorporated into a peptide backbone and served as conformational constraints. The scope and limitation of the ring formation were studied, and the structural requirements and reaction conditions for cyclization are outlined.